Detection of the Effects of Hexagon Fraud Theory on Financial Statement Fraudulent - Ramadhanty, Aisyah Putri; Septiani, Tika (Yayasan Ilomata, 2024)
The incidence of fraud has been increasing steadily over the years, with the most detrimental kind being financial statement fraud, leading to significant losses for both the company and the users of financial statements. The results of research provide information about the possibility of corporate fraud for the investors and the stakeholders to take better conclusions. Two very popular concepts for identifying profit manipulation in companies and understanding the motivations of fraud are the M Beneish model and fraud theory. The population used in research is 128 Financial Companies Listed on the IDX for the 2022-2023 period. The method used in this research is quantitative research method and uses logistic regression analysis in analyzing data. The results showed that financial targets and external pressures, ininfluenceive supervision, CEO tenure, Arrogance and collusion had no influence on financial reporting fraud. However, total accrual ratio has an influence on fraudulent financial statements.